Revealing antibiotic resistance’s ancient roots: insights from pristine ecosystems - Agudo, Rubén; Reche, M. Paloma (Frontiers in Microbiology, 2024)
The prevailing belief that antibiotic resistance mechanisms emerged with human antibiotic use has been challenged. Evidence indicates that some antibiotic resistance genes (ARGs) have a long evolutionary history, predating the advent of antibiotics in human medicine, thereby demonstrating that resistance is an ancient phenomenon. Despite extensive surveys of resistance elements in environments impacted by human activity, limited data are available from remote and pristine habitats. This minireview aims to compile the most relevant research on the origins and evolution of ARGs in these habitats, which function as reservoirs for ancient resistance mechanisms.These studies indicate that ancient ARGs functionally similar to modern resistance genes, highlighting the general role of natural antimicrobial substances in fostering the evolution and exchange of diverse resistance mechanisms through horizontal gene transfer over time. This minireview underscores that antibiotic resistance was present in ancestral microbial communities and emphasizes the ecological role of antibiotics and resistance determinants. Understanding ancient ARGs is crucial for predicting and managing the evolution of antibiotic resistance. Thus, these insights provide a foundational basis for developing new antibiotics and strategies for microbial resistance management.